Analytical model for compressive arch action in unbonded prestressed concrete beam-column subassemblages under a column-loss scenario. (15th December 2022) - Tao, Yuxuan; Huang, Yuan; Yi, Weijian
Highlights: A RC and four unbonded prestressed concrete (PC) beam-column subassemblages are tested. An analytical model is developed to determine the compressive arch action capacity of PC frames. The compressive strain of the reinforcement can be obtained in the proposed model. The model considers the impacts of span-depth ratio, boundary conditions, tendon profiles, initial prestress et al. The effects of unbonded prestressed tendon profiles on the progressive collapse mechanism of PC frames are elaborated. Abstract: This study investigates the progressive collapse behavior of unbonded prestressed concrete (PC) beam-column subassemblages with different unbonded prestressed tendon (UPT) profiles subjected to the loss of a middle column. Then, in accordance with the compatibility and equilibrium conditions, an analytical model is developed to determine the compressive arch action (CAA) capacity of PC frames considering the effect of boundary conditions and UPT profiles. The developed model can effectively reflect the influence of the prestressed force and tendon profiles on the CAA capacity of PC frames by considering the interaction between the UPTs and structures. Furthermore, the effect of UPT profiles on the progressive collapse mechanism of PC frames is elaborated. Analytical results indicate that the UPTs are a dominant source for the CAA capacity of PC frames. The CAA capacity is sensitive to variation in UPT profiles because the UPTs change the axial force and moment of beams.